Contact time, flight time and ground reaction forces during a controlled running trial of elite american football players - Mokha, M.; Peacock, C.; Bommarito, P. (ISBS Proceedings Archive (Michigan), 2018)
Running speed is influenced by vertical ground reaction force (vGRF) application, foot-ground contact time (Tc), flight time (TF), and time taken to reposition the limbs in swing. The purpose of this study was to investigate running speed modulators in two groups of elite American football players [Skill (i.e. wide receivers, defensive backs, n=8) and Big Skill (i.e. linebackers, tight ends, n=8)]. Subjects ran at 6.5 m/s for 5 sec on an instrumented treadmill. Peak vGRF, Tc and TF were examined for overall associations and compared between groups. Tc was strongly associated with vGRF, p<.001. Big Skill had larger absolute vGRF, p=.012 than Skill. Skill players had larger TF, smaller TC, and smaller relative vGRF, although not significant. Elite American football players apply large forces over long foot-ground contact time during a controlled run